2022
DOI: 10.1136/bmj-2022-071375
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of extended duration to perioperative thromboprophylaxis with low molecular weight heparin on disease-free survival after surgical resection of colorectal cancer (PERIOP-01): multicentre, open label, randomised controlled trial

Abstract: Objective To determine the efficacy and safety of extended duration perioperative thromboprophylaxis by low molecular weight heparin when assessing disease-free survival in patients undergoing resection for colorectal cancer. Design Multicentre, open label, randomised controlled trial. Settings 12 hospitals in Quebec and Ontario, Canada, between 25 October 2011 and 31 December 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Similarly, this study also found that different types of anemia were closely related to tumor location, tumor size, and TNM stage, consistent with Giudice & Selleri ’s ( 2022 ) study. Auer et al (2018) also found that compared with the distal colon and rectum, the hemoglobin of patients with proximal colon tumors was significantly lower. Disturbance of colonic microbiota can lead to the occurrence and development of colorectal cancer and interfere with the absorption of nutrients ( Gomes et al, 2022 ).…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, this study also found that different types of anemia were closely related to tumor location, tumor size, and TNM stage, consistent with Giudice & Selleri ’s ( 2022 ) study. Auer et al (2018) also found that compared with the distal colon and rectum, the hemoglobin of patients with proximal colon tumors was significantly lower. Disturbance of colonic microbiota can lead to the occurrence and development of colorectal cancer and interfere with the absorption of nutrients ( Gomes et al, 2022 ).…”
Section: Discussionmentioning
confidence: 84%
“…In our study we did not investigate the survival difference between prolonged perioperative anticoagulation and postoperative anticoagulation alone. One study reported that prolonged perioperative anticoagulation did not improve DFS or OS in patients with colorectal cancer undergoing surgical resection compared with in-hospital postoperative thromboprophylaxis [34]. The optimal timing of anticoagulation therapy in patients with GC needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“… 54 , 55 , 56 This finding from our meta-analysis is further supported by a recently published randomized controlled trial enrolling 614 adults with colorectal cancer comparing extended (8 weeks) to inpatient-only tinzaparin administration after surgical resection, which was halted for futility with no difference in 3-year disease-free survival or 5-year overall survival. 57 …”
Section: Discussionmentioning
confidence: 99%